2016
DOI: 10.1103/physrevlett.116.033602
|View full text |Cite
|
Sign up to set email alerts
|

Partially Nondestructive Continuous Detection of Individual Traveling Optical Photons

Abstract: We report the continuous and partially nondestructive measurement of optical photons. For a weak light pulse traveling through a slow-light optical medium (signal), the associated atomic-excitation component is detected by another light beam (probe) with the aid of an optical cavity. We observe strong correlations of g ð2Þ sp ¼ 4.4ð5Þ between the transmitted signal and probe photons. The observed (intrinsic) conditional nondestructive quantum efficiency ranges between 13% and 1% (65% and 5%) for a signal trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In our analysis, we have assumed that all atoms are equally coupled to the cavity field. For uneven couplings, if the atoms are subject to a uniform driving Ω and do not move, the dynamics are expected to resemble the homogeneous case and we thus expect similar results also for inhomogeneous coupling [37,41,42]. An extension of this work would be to include fluctuating couplings of the atoms, which e.g.…”
Section: Conclusion and Discussionsupporting
confidence: 57%
“…In our analysis, we have assumed that all atoms are equally coupled to the cavity field. For uneven couplings, if the atoms are subject to a uniform driving Ω and do not move, the dynamics are expected to resemble the homogeneous case and we thus expect similar results also for inhomogeneous coupling [37,41,42]. An extension of this work would be to include fluctuating couplings of the atoms, which e.g.…”
Section: Conclusion and Discussionsupporting
confidence: 57%
“…Non-destructive detection of optical photons is also being pursued with atomic ensembles, and large single-photon phase shifts mediated by laser-cooled atomic vapour have recently been reported using both Rydberg blockade9 and the a.c. Stark shift in a high-finesse cavity10. The latter system has furthermore enabled partial non-destructive detection of traveling photons11. These investigations are part of the general drive of using atomic ensembles to mediate strong photon–photon interactions1213, for example, via strong long-range dipole–dipole interaction between Rydberg atoms14 or via the a.c. Stark shift1516.…”
mentioning
confidence: 99%
“…The experiment is performed with an ensemble of cold atoms in a cavity in the strong-coupling regime [20][21][22][23]. Previously, using a similar setup, we have shown that a measurement of the ancilla mode can project the input coherent state of the signal mode into a single-photon Fock state [24], and demonstrated that the phase of the signal light could be changed by about π=3 by a single ancilla photon transmitted through the cavity detuned from the atomic resonance [17]. In the current realization, we observe an anomalous and large conditional phase shift of the signal state in a near-resonant regime where the average phase shift is almost zero.…”
mentioning
confidence: 99%
“…When we operate on cavity and atomic resonance, t is given by t ¼ 1=ð1 þ ηÞ, where η ¼ 8.6 is the single-atom cooperativity [24].…”
mentioning
confidence: 99%